Self-control, chronotype, and future time perspectives as predictors of bedtime procrastination among Malaysian young adults - Law, Isaac Lik Jun; Leong, Syn Jieh; Tan, Hor Yinn (2023)
Bedtime procrastination, a behaviour of voluntarily delaying bedtime by sleeping later than the intended time, is a prevalent issue in modern society, yet being understudied in the Malaysian context. It brings health-interfering impacts such as sleep deficiency, which in turn could affect the physical and mental health of the individual. This research aims to study the predictive effects of self-control, chronotype and future time perspective on bedtime procrastination among young adults in Malaysia. This study hypothesised that self-control, chronotype and future time perspective could negatively predict bedtime procrastination. Quantitative cross-sectional study design was implemented. Convenience sampling method was employed for data collection by distributing the Qualtrics online survey on platforms such as Facebook, Instagram, WhatsApp, Wechat, and Xiaohongshu. Bedtime Procrastination Scale (BPS), Brief Self-Control Scale (BSCS), Morningness-Eveningness Questionnaire (MEQ), and Zimbardo Time Perspective Inventory (ZTPI) Future Subscale were administered in this study. The participants are Malaysian young adults between 18 and 29 who are not working on shift or having sleep problems. The final total number of responses included in the study is 108. Multiple Linear Regression analysis was run to test the hypotheses of the study. The findings revealed that self-control significantly and negatively predicts bedtime procrastination, while chronotype significantly and positively predicts bedtime procrastination. However, future time perspective is not a significant predictor of bedtime procrastination. This study provides insights into the concept of bedtime procrastination and a direction for future studies to further explore the underlying factors of bedtime procrastination. It also provides information for practitioners to design effective interventions to reduce bedtime procrastination.